"Semente" skills through the project methodology (Journal of Parents and Teachers, 2013)
This article guides us through active methodologies and their contribution to the development of core competences by carrying out projects in the classrooms with children in second grade of Primary Education. This concept is integrated in a project called “Proxecto Semente”. “Proxecto Semente” was an initiative based on the creation and management of a cooperative company in which to elaborate products that, later on, would be sold on a school market.  The children developed habits and enterprising behaviors. The learning processes were necessary for the good management of the company, which needed to have integrated different knowledges and matters in a coherent and practical way, so that it was easy for everyone to see the use of all the capacities that they were developing: communication, analysis of the environment, cohabitation, citizenship…
Keywords: Competences; Primary Education; Teaching and training; Project method; didactic